Compensation with hybrid active power filter in an industrial plant - Corasaniti, Víctor Fabián (2013)
This paper presents the application of a hybrid active power filter for reactive and harmonic compensation at the level of Medium Voltage (MV) of an electrical network of an industrial plant. It is considered as control algorithm, the application of the d-q theory and performing the current measuring in the system, establishing a feedback control loop (feedback). It is analyzed a hybrid topology called Shunt Hybrid Active Power Filter "SHAPF". This proposal uses an existing capacitor bank, transformed into a passive filter, and connected in series with the Active Filter to build a hybrid filter in which the compensation supplement is made by the active filter. We analyze different scenarios of operation. The topology has very good performance under steady state and transient.